The use of the concept of tooth material as an indication of tooth size in a group of Kalahari Bushmen - Van Reenen, J. F. (My University, 1961)
The limitations of Fowler's dental index are discussed. A new concept of tooth size is defined using the measurement "tooth material" as proposed by Ashley E. Howes. In the case of groups or races, the mean total tooth material of both arches is used to determine the size of the dentition. According to this concept, the Kalahari Bushmen of the present study are microdont. Material published by other investigators is also used to classify other groups according to this new concept of tooth size.
PK
Keywords: White Coat tooth coating material; Tooth